Comparison of Two Organic Trace Mineral Supplements for Cows Grazing Tall Fescue - J. K. Farney (Kansas Agricultural Experiment Station Research Reports, 2017)
The purpose of this study was to determine the effects of two sources of organic trace mineral and two sources of magnesium supplementation on cow performance of springcalving cows on K31 endophyte-infected fescue. The two treatments were organic trace minerals (zinc (Zn), copper (Cu), and manganese (Mn)) offered free choice as an amino-acid chelate with magnesium (Mg) as an amino acid chelate (CHEL) or organic trace mineral supplement with amino-acid complex with magnesium supplied as magnesium oxide (COMP). Mineral was offered free-choice beginning 30 days before breeding season on 4 ranches with 6 pastures per treatment (cows n = 203). Blood samples were collected prior to mineral supplementation and at pregnancy evaluation and serum was analyzed for Mg, Zn, Cu, and Mn. One ranch had an anaplasmosis event, therefore analysis was completed with and without this ranch. Pregnancy rate was not different (P = 0.46) when all 4 ranches were analyzed even though pregnancy rates were 89.3 and 92.9% for COMP and CHEL, respectively. Cows on the COMP mineral calved 6 days earlier (P = 0.04). When removing the anaplasmosis ranch, pregnancy rate was closer to approaching a tendency for a difference (P = 0.15) with pregnancy rates of 95.5 and 87.2% for CHEL and COMP, respectively, with a tendency (P = 0.12) for COMP cows to calve 5 days earlier. All serum mineral levels were lower at pregnancy detection than initial blood draw primarily due to reduction in mineral levels in fescue late in summer and a reduction in intake at the end of the project. Serum Mg tended (P = 0.11) to stay more stable with the CHEL mineral such that the difference in final and initial Mg were similar. Serum Zn, Cu, and Mn were not different (P>0.10) with the exception of some ranch-to-ranch variations. Additionally, CHEL intake was 6% lower than COMP. Even with the lower intake of the CHEL mineral, serum mineral levels were similar between both treatments; this indicates that CHEL minerals are more bioavailable. Overall, chelated minerals appear to provide an advantage to spring-calving cows on K31 fescue especially from a chelated magnesium source.
Keywords: endophyte; spring-calving; serum mineral; amino acid complex; amino acid chelate